PENYULUHAN HUKUM JAMINAN KEHILANGAN PEKERJAAN KEPADA MASYARAKAT PANCORAN, JAKARTA SELATAN - Rospita Adelina Siregar; Ani Wijayati; I Dewa Ayu Widyani; Haposan Sahala Raja Sinaga (Universitas Methodist Indonesia, 2022)
Community Service (PkM) is carried out by the Faculty of Law Universitas Kristen Indonesia by providing legal counseling about job loss guarantees by the government for workers/labourers who have been laid off due to the Covid-19 pandemic. PkM will be held on 18 December 2021 at Pancoran Buntu II, Pancoran Village, Pancoran District, South Jakarta. The method used is to provide counseling/lectures and provide motivation, then followed by question and answer to obtain results and solutions as a form of solving problems and obstacles faced. At the time of providing counseling/lectures, special tables are also provided to receive personal legal consultations for the community. The results of PkM with legal counseling are very effective considering that there are still many people who do not get information on job loss guarantees provided by the Government through PP No. 37 of 2021 concerning the Implementation of the Job Loss Guarantee Program. With this legal counseling, the public becomes aware of this program and what benefits can be obtained, such as cash benefits, access to job information, and job training. Thus, it is hoped that the people of Pancoran who have lost their jobs / have been laid off are always motivated to maintain a decent standard of living by wanting to work again or try to be independent.